2022
DOI: 10.1002/nau.24978
|View full text |Cite
|
Sign up to set email alerts
|

Urethral pressure profile before radical prostatectomy as a predictor of early postoperative continence

Abstract: Objective: Urinary incontinence (UI) is one of the most common complications of radical prostatectomy (RP). Impaired urethral sphincter function is generally considered to be the most important contributing factor for UI; however, the mechanism of onset and recovery of urinary continence has not been fully elucidated. The objective of this research was to evaluate preoperative functional urethral length (FUL) and maximum urethral closure pressure (MUCP) as early continence recovery predictors after open retrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In order to properly assess it, different methods can be used from magnetic resonance imaging to obtain anatomical data and urodynamic studies to add functional information's regarding pressure values before and/or after the surgery. (14,15) However, these methods can add additional costs, time and burden for the patients and therefore are not used often. With the introduction of minimally invasive procedures, we have new methods which can be used to assess preserved part of the urethra by using semi-quantitatively measured on a video screen which have confirmed that patients with longer preserved urethral length have a significantly higher rate of post-operative urinary continence recovery.…”
mentioning
confidence: 99%
“…In order to properly assess it, different methods can be used from magnetic resonance imaging to obtain anatomical data and urodynamic studies to add functional information's regarding pressure values before and/or after the surgery. (14,15) However, these methods can add additional costs, time and burden for the patients and therefore are not used often. With the introduction of minimally invasive procedures, we have new methods which can be used to assess preserved part of the urethra by using semi-quantitatively measured on a video screen which have confirmed that patients with longer preserved urethral length have a significantly higher rate of post-operative urinary continence recovery.…”
mentioning
confidence: 99%